LENGTH-WEIGHT RELATIONSHIP OF EIGHT SPECIES OF FISH CAUGHT BY TRADITIONAL PAPUAN FISHERS IN YOUTEFA BAY, INDONESIA - Hamuna, Baigo; Indrayani, Ervina; Agamawan, Lalu Panji Iman (European Journal of Ecology, 2023)
In this study, data on length and weight of fish were used to determine the length-weight relationship and condition factors of eight fish species that are targeted by traditional Papuan fishers and have high economic value (Lutjanus fulvus, Gerres oyena, Parupeneus barberinus, Siganus spinus, Siganus canaliculatus, Pelates quadrilineatus. Mugil cephalus, and Hemiramphus far) in Youtefa Bay, Papua Province, Indonesia. A total of 245 fish specimens were collected from Papuan fishermen during the period January to March 2020. The total length and body-weight of the fish specimens studied ranged from 15.2 to 32.1 cm (average 20.26±3.73 cm) and 42.72 to 371.86 g (average 124.10±52.45 g), respectively. The b value ​​for all fish species studied ranged from 2.6919 to 3.0791, with the coefficient of determination (R2) ranging from 0.9022 to 0.9947. The growth patterns of the eight fish species were allometric (b ≠ 3; t-test < t-tab), where L. fulvus (2.824), P. barberinus (2.9136), S. canaliculatus (2.989), P. quadrilineatus (2.9577), M. cephalus (2.9096), and H. far (2.6919) were negative allometric (b < 3), while G. oyena (3.0596) and S. spinus (3.0791) are positive allometric (b > 3). Meanwhile, the relative condition factor and Fulton condition factor values ​​ranged from 0.874 to 1.201 (average 0.999±0.321) and 0.204 to 2.726 (average 1.612±0.515). M. cephalus had a higher relative condition factor, while L. fulvus had a higher Fulton condition factor than other fish species